The multi-tier mecanism and the Dispute Avoidance resolution into the collaborative environment proposed by the New Engeniering Contract 4 (NEC4) - Lama Bustinza, José Andrés (2020)
In the midst of the need to find effective and efficient mechanisms for solving disputes in construction projects, this article analyzes the proposal dealing with the multi-tier mechanisms along with the dispute avoidance board, a proposal that runs as part of a collaborative environment (and not the inaccurate idea of a “collaborative contract”), set up by the recently edited-NEC 4. The text offers to the reader the chance to consider, based on their experience and the exposed concepts in the text, a useful and ad-hoc scene using both tools, according to the needs of the project. This article proposes a way of understanding and using the mechanisms offered by the NEC 4 Contract, and especially in relation to the multitier mechanism and the Avoidance Dispute Board, in order to achieve the goals of efficiency in the execution of a project and avoiding what has happened with another mechanisms, which were considered in practice as merely formal steps prior to a definitive solution.